Regulation of CsrB/C sRNA decay by EIIA(Glc) of the phosphoenolpyruvate: carbohydrate phosphotransferase system - Leng, Yuanyuan (Mol Microbiol, 2015)
Csr is a conserved global regulatory system, which uses the sequence specific RNA binding protein CsrA to activate or repress gene expression by binding to mRNA and altering translation, stability and/or transcript elongation. In Escherichia coli, CsrA activity is regulated by two sRNAs, CsrB and CsrC, which bind to multiple CsrA dimers, thereby sequestering this protein away from its mRNA targets. Turnover of CsrB/C sRNAs is tightly regulated by a GGDEF-EAL domain protein, CsrD, which targets them for cleavage by RNase E. Here, we show that EIIA(Glc) of the glucose-specific PTS system is also required for the normal decay of these sRNAs and that it acts by binding to the EAL domain of CsrD. Only the unphosphorylated form of EIIA(Glc) bound to CsrD in vitro and was capable of activating CsrB/C turnover in vivo. Genetic studies confirmed that this mechanism couples CsrB/C sRNA decay to the availability of a preferred carbon source. These findings reveal a new physiological influence on the workings of the Csr system, a novel function for the EAL domain, and an important new way in which EIIA(Glc) shapes global regulatory circuitry in response to nutritional status.